OPTIMALISASI PEMANFAATAN SAYURAN HIDROPONIK MENJADI PRODUK COOKIES DAN MIE KERING KAYA GIZI OLEH KELOMPOK WANITA TANI (KWT) GUMUKREJO KABUPATEN PRINGSEWU - Ambar Wati, Desti; Muharramah, Alifiyanti (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
This activity was motivated by the main activity of the Kelompok Wanita Tani (KWT) Gumukrejo, Pagelaran Regency is hydroponic cultivation of vegetable plants. Hydroponics is a plant cultivation technique that uses water as a growing medium which contains certain levels of nutrients and oxygen. Several types of vegetable plants that have been cultivated by KWT Gumukrejo members are lettuce, bok choy, kale and red spinach. So far, the results of vegetableproduction have been processed without modification or in the form of processed food or products that have high selling value. This KWT has never received information related to the use of vegetable plants from hydroponiccultivation production into processed food or food products, namely noodles and cookies. Modification of this product is by substitution of cultivated vegetable plants. This food product is easy to make, has a longer shelf life, has high nutritional value and high economic value. The implementation stages include outreach and education activities to provide understanding to partners regarding the results of situation analysis regarding the use of hydroponic vegetables and training in making processed food products from hydroponic vegetable plants. The implementation time for this activity will be carried out for 1 month in December 2022 – January 2023. The target of this activity is all 15 members ofthe Kelompok Wanita Tani (KWT). Program evaluation for this activity was carried out by analyzing the level of knowledge and skills of all KWT members using pre-test and post-test instruments. The program sustainability plan withpartners is expected to be able to carry out product development independently by accepting orders from consumers, marketing using social media.